Effect of Structured Workers Physical Exercise, Individual Factors, and Work-related Factors on Physical Fitness of Security Officers - Rosady, Dony Septriana; Mirtha, Listya Tresnanti; Agustina, Amilya; Soemarko, Dewi Sumaryani; Sugiharto, Agus (Universitas Islam Bandung, 2025)
Security officers require good physical fitness to perform their duties effectively. Maintaining this level of fitness often involves structured exercise programs that consider the frequency, intensity, duration, and type of activity. This study aims to examine the relationship between a structured physical exercise program, individual factors, and work-related factors on the physical fitness of security officers. This study was conducted in July 2023 and utilized company program data from March to June 2023, focusing on 67 security officers at PT X. Physical fitness data was collected using the Cooper test method and analyzed using SPSS. Data normality was assessed using the skewness/standard error method, with values <2 considered normally distributed. A paired sample t-test revealed a significant relationship between Cooper test distances before and after participation in the structured exercise program (p<0.001). Further analysis demonstrated relationships between changes in physical fitness and several factors: work fatigue (p<0.001), work stress dimensions (specifically work overload, role conflict, quantitative and qualitative workload excess, career development, and responsibility to others, all with p<0.014), and sleep quality (p<0.001). The coefficient of determination (r2) was 0.496, indicating that work fatigue, role conflict, and sleep quality collectively explain 49.6% of the variance in physical fitness changes. The remaining variance is likely influenced by factors not included in the model. Multivariate analysis confirmed that work fatigue (p<0.001), role conflict (p=0.036), and sleep quality (p=0.015) were predictors of changes in physical fitness. In conclusion, a structured physical exercise program has a positive influence on the physical fitness of security officers. Furthermore, work fatigue, work stress (particularly role conflict), and sleep quality are associated with changes in physical fitness among these officers.